The Deaves Affair - Footner, Hulbert, 1879-1944 (Salt Lake City, UT : Project Gutenberg, 2010)
"The Deaves Affair" by Hulbert Footner is a novel written in the early 20th century. The story revolves around Evan Weir, a struggling artist, and his encounters with the eccentric millionaire Simeon Deaves. The plot unfolds as Evan becomes inadvertently embroiled in a blackmail scheme targeting Deaves, leading him to navigate the complexities of privilege, class, and personal integrity. The opening of the novel introduces Evan, who is frustrated with his artistic endeavors and seeks inspiration outside his attic studio. His day takes a peculiar turn when he witnesses an amusing yet charged confrontation involving the old miser Simeon Deaves, who is scorned by a crowd for his stingy ways. As Evan intervenes to help Deaves, the narrative hints at Evan's journey to both find meaning in his life and to uncover the tangled web of deception surrounding the wealthy family. The initial chapters lay the groundwork for a comedic yet incisive exploration of societal values, ambition, and the unexpected bonds formed amidst chaos. (This is an automatically generated summary.)
Release date is 2010-02-22
Produced by Al Haines
Keywords: Detective and mystery stories